Critique of Secular Western Science from the Perspective of Islamic Education - Ahmad Nanda Maulana; Nanat Fatah Natsir; Erni Haryanti; Muhammad Alif Ramadhan; Siti Wifa Uswatussolihah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper describe critics about secularism in Western science, which separates religion from worldly aspects of life, emphasizing objectivity without the influence of religious values. This view contradicts Islamic Education, which integrates religious teachings in shaping individuals who are faithful, pious, and of noble character. The process of secularization shifts society away from spiritual values, creating gaps in understanding, especially in education. Islamic education focuses on the harmony between religion and science, unlike the secularist view that separates the two. As a result, secularism influences future generations to solve problems without considering religious values, which contradicts the holistic principles of Islam.